Corporate strategy in multinational environments: Carvajal S.A. case - González Calixto, Mónica Bibiana (Universidad Pedagógica y Tecnológica de Colombia, 2011)
This case allows a deeper understanding of corporate strategies in multinational environments, through the study of the Colombian company CarvajalS.A., which reflects a harmony between what we want to become and what it is. Thus, their strategy has enabled it to make better competitive position. By tracking the historical development and from information obtained from the company and previous studies in the same, are identified and validated multinationalization strategies it has implemented to settle in a global environment, which sets out what were the powers that have different and that stand out internationally and discusses how the company has aligned with the global requirements of transparency and management of its corporate governance. To maintain and improve its position in a global environment, this company can among other things, issue shares, analysis of attractiveness, strengthen your marketing strategies, improve knowledge transfer processes, leverage resources, think globally and continue to innovate.